Efficacy of antibiotic short course for bloodstream infections in acute myeloid leukemia patients with febrile neutropenia: A retrospective comparative study. Issue 1 (January 2022) - Metais, Agathe; Torregrosa Diaz, Jose Miguel; Gallego Hernanz, Maria Pilar; Pichon, Maxime; Desmier, Deborah; Roblot, France; Rammaert, Blandine
Abstract: Objectives: There is no specific recommendation about antimicrobial treatment length for documented infections in chemotherapy induced febrile neutropenia (FN). Practices have changed along time in our center regarding length of antibiotic treatment. The aim of this study was to compare long versus short antibiotic course for bloodstream infection (BSI) treatment in acute myeloid leukemia (AML) patients during FN. Methods: This monocentric retrospective comparative study included all consecutive BSI episodes among AML patients with FN for 3 years (2017–2019). Episodes were classified regarding the length of antibiotic treatment, considered as short course if the treatment lasted ≤ 7 days, except for nonfermenting bacteria and Staphylococcus aureus or lugdunensis for which the threshold was ≤ 10 days and ≤ 14 days, respectively. The primary outcome was the number of BSI relapses in both groups within 30 days of antibiotic discontinuation. Results: Among 71 AML patients, 104 BSI episodes were included; 48 (46%) received short course treatment. Only 8 (7.6%) BSI episodes relapsed within 30 days of antibiotic discontinuation, 5 having received short course treatment. No association was found between risk of relapse and short course of antibiotic treatment ( p = 0.37). The only risk factor significantly associated with BSI relapse was neutropenia duration ( p = 0.005). Conclusion: Antibiotic short course seemed as effective as prolonged treatment for BSI in AML patients during FN, with very few relapses at day 30. These encouraging findings should be confirmed through prospective studies.